10.1016/s1544-8800(08)70219-7 (CrossRef Listing of Deleted DOIs, 2000)
Objectives The World Health Organization's (WHO) Global Network of Age-Friendly Cities and Communities (AFCCs) promotes the development of urban environments, policies and services that support the health and participation of older adults. This systematic review examined contemporary evidence concerning associations between WHO AFCC conditions and directly measured health and physical activity outcomes among older residents. Methods The registered review adhered to the PRISMA protocol for systematic reviews and meta-analyses and applied the Downs and Black quality criteria for randomised and non-randomised research. Results Structured Boolean searches of five research repositories identified 17 peer-reviewed studies published between 2017 and 2025 based upon original research conducted in WHO AFCC signatory cities. Although most studies reported positive associations between age-friendly features and domains, such as accessible transport, walkable environments, outdoor infrastructure and self-rated health or physical activity, the strength of evidence was limited by methodological inconsistency, variable study quality and reliance on self-reports. Barriers to evaluation included limited use of longitudinal or quasi-experimental designs, heterogeneous outcome measures, subjective response data and the challenge of establishing appropriate comparison conditions in complex municipal settings. Conclusions Strengthening evaluation frameworks for AFCC initiatives is essential for evidence-based urban health policy and governance in rapidly ageing societies. A research agenda is proposed to strengthen AFCC evaluation through standardised measurement, community-based and mixed-methods research, and a greater commitment to co-designed assessment frameworks.